2015
DOI: 10.1002/ajim.22462
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures and risk of dementia‐related mortality in the prospective Netherlands Cohort Study

Abstract: Consistent positive associations were found between occupational exposure to metals and non-vascular dementia. The finding on pesticides is not supported in the overall literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Our findings are in line with those previously reported in occupational cohorts, mainly showing detrimental effect in the areas of processing speed and attention 9. Our results are also in agreement with those from the prospective cohort of French national gas and electricity (GAZEL) employees (n=2143 men)6 or from the prospective Netherlands cohort study (n=2411 men) 35. The consistent associations found for the DSST score are particularly interesting because this cognitive test is likely to be one of the most appropriate to examine cognitive performance in younger persons; it is a sensitive test36 requiring sustained attention, processing speed and visual spatial skills, and poor performance on this test has been linked to incident dementia 37…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with those previously reported in occupational cohorts, mainly showing detrimental effect in the areas of processing speed and attention 9. Our results are also in agreement with those from the prospective cohort of French national gas and electricity (GAZEL) employees (n=2143 men)6 or from the prospective Netherlands cohort study (n=2411 men) 35. The consistent associations found for the DSST score are particularly interesting because this cognitive test is likely to be one of the most appropriate to examine cognitive performance in younger persons; it is a sensitive test36 requiring sustained attention, processing speed and visual spatial skills, and poor performance on this test has been linked to incident dementia 37…”
Section: Discussionsupporting
confidence: 93%
“… “For lead exposure there are no data supporting any association. All the studies are case–control studies, with a relatively low level of quality according to our classification.” (p. 730) - Koeman et al 2015 [ 63 ] Metals (occupational exposure) The Netherlands Cohort Study which consisted of 120,852 individuals aged 55–69 years in 1986. 682 men and 870 women who had died with non-VaD reported on their death certificates over 17 years follow up.…”
Section: Resultsmentioning
confidence: 99%
“…Vergara et al (2013) found no indication of an association with dementia (RR 1.05, 95% CI 0.96-1.14) based on nine studies, but they did not distinguish between different levels of exposure. In a recent cohort study in the Netherlands, Koeman et al (2015) found an association between high occupational ELF-MF exposure and non-vascular dementia-related mortality in men (RR 1.40, 95% CI 0.92-2.14), however, not with cumulative exposure. Koeman et al (2015) concluded that the observed association was likely to be attributed to exposure to metals, with which the ELF-MF exposure was highly correlated.…”
Section: Comparison With Previous Follow-ups In the Cohort And Other mentioning
confidence: 92%